Kegiatan Donor Darah Sebagai Gerakan Sosial Di Jurusan Teknik Kimia ITATS - Erlinda Ningsih; Kartika Udyani; Dian Yanuartita P.; Axo Syamboga; Mohammad Arjun Santoso; Dwi Setiawan (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Blood donation is an activity where a person voluntarily gives blood which will later be stored in a blood bank for transfusion purposes for those in need. Generally, blood requirements are not proportional to the number of donors. Information on the importance of the danar donors is still unknown. This activity aims to help the Surabaya City Indonesian Red Cross meet and increase the blood stock needed in the city of Surabaya and to socialize all students of the Surabaya Adhi Tama Institute of Technology about the importance of blood donation. This blood donation activity is a collaboration between the Chemical Engineering Student Association and the Indonesian Red Cross Donor City of Surabaya. The technical implementation of this activity is divided into 4 stages, namely distribution of donor forms, donor registration, health checks, blood donors. This blood donation activity is supported not only by the chemical engineering community, but also by the faculty community, namely students and lecturers. The blood donation activity lasted for 1 day with 60 blood donor participants and it went well. The participants involved consisted of 52 students and 8 lecturers. Based on the health check, it was found that 40 participants did not meet the requirements to become blood donors and 20 people did, so they received 20 bags of blood.